Anodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex improves attentional control in chronically stressed adults - Liu, Yong; Liu, Qingjin; Zhao, Jia; Leng, Xuechen; Han, Jinfeng; Xia, Feng; Pang, Yazhi; Chen, Hong (Frontiers in Neuroscience, 2023)
Introduction Chronic stress is a long-term condition that negatively affects cognitive ability and mental health. Individuals who experience chronic stress show poor attentional control. Transcranial direct current stimulation (tDCS) to the dorsolateral prefrontal cortex (DLPFC) modulates executive function domains. Therefore, it is beneficial to investigate whether tDCS of the DLPFC could improve attentional control and relieve stress in chronically stressed individuals. Methods We assess the event-related potentials (ERPs) associated with attentional control in individuals with chronic stress after the tDCS intervention. Forty individuals were randomly assigned to either the anodal tDCS group, which received 5 sessions of the 20 min tDCS over the DLPFC (2 mA; n = 20), or the sham tDCS (n = 20). Participants’ stress levels, anxiety, depressive symptoms, and state affects were assessed and compared before and after the intervention. The ERP was collected through electroencephalography (EEG) technology during an attentional network test. Results After the anodal tDCS, we found a significant decrease in the perceived stress scale (PSS) scores (from an average score of 35.05 to 27.75), p = 0.01 as well as the State-Trait Anxiety Inventory (STAI) scores, p = 0.002. Better performance in the attentional network test, a significant reduction in the N2 amplitudes, and an enhancement in the P3 amplitudes (both cues and targets) were also found in the anodal tDCS group. Discussion Our study findings suggest that tDCS to the left DLPFC could effectively relieve chronic stress, potentially reflected by increased attentional control.